Characteristics analysis for clinical study design relating to COVID-19 based on the database of ClinicalTrials.gov. (March 2022) - Wu, Hanting; Dai, Rongchen; He, Peijie; Liang, Juan; Li, Qiushuang; Yang, Junchao; Lu, Hanti; Guo, Qing; Mao, Wei; Ji, Conghua
Highlights: ClinicalTrials.gov is searched for the design schemes of all COVID-19 research. We analyze the difference of characteristics between COVID-19 trials and others. The proportion of randomized controlled trials is high in COVID-19 trials. Observational COVID-19 trials have a higher completion rate than others. The importance of an appropriate study design is disclosed. Abstract: Background and Objective: The novel coronavirus disease (COVID-19) outbreak is currently ravaging populations worldwide. Many studies were registered and conducted in rapid response to the epidemic, but how to choose the proper design for clinical trials remains the main concern. This study aimed to determine the fundamental characteristics of study design during the COVID-19 pandemic and provide references for other emerging infectious diseases. Methods: We searched the database of ClinicalTrials.gov with the keyword "COVID-19" and compared the results with the design features of other conventional studies except for COVID-19. Results: From January 1, 2020 to September 30, 2021, 55, 334 trials were registered at ClinicalTrials.gov. Of all the registered trials, 6, 408 were related to COVID-19 (11.58%). There were significant differences in the proportion of observational studies between COVID-19 (43.48%) and others (23.27%). The completion rate of observational trials and interventional trials in COVID-19 was 29.04% and 25.84%, respectively. COVID-19 trials showed a higher rate of completion than others (P<0.01). The time distribution and trend of observational studies and interventional studies varied considerably. Conclusion: Appropriately designed trials can help to improve research efficiency and reduce the possibility of research failure. In addition to randomized controlled trials, observational and single-armed studies are also worth considering.